e-Wom Jamu pada Konsumen Milenials (Studi Eksplanatif Brand Image dan Purchase Intention pada Produk Jamu Indoherbal) - Gatot Sugih Budiono; Niken Febrina Ernungtyas; Guntur Freddy Prisanto; Irwansyah Irwansyah; Anindita Lintangdesi Afriani (Universitas Merdeka Malang, 2020)
Marketing of products and services is becoming faster with the support of internet technology. This is realized by the company of Asraza Indoherbal, one of the Indonesian herbal medicine producers that conduct online marketing through social media Facebook and also websites. This company has realized the importance of creating a brand image and online marketing that can increase the buying interest of potential consumers. This study aims to analyze the effect of E-WOM on Brand Image of Asraza Indoherbal, the effect of E-WOM on Purchase Intention Asraza Indoherbal, and the influence of Brand Image Asraza Indoherbal on Millennial generation Purchase Intention. This research was conducted using a survey aimed at 100 respondents of the millennial generation scattered in several cities in Indonesia. The results revealed that there was an influence of e-WOM on brand image, there was no effect of e-WOM on purchase intention, and there was an effect of brand image on purchase intention. Keywords: e-WOM, Brand Image, Purchase Intention, Social Media, Millennial